PERANAN PENJUALAN KREDIT TERHADAP MODAL KERJA DAN PERKEMBANGAN PENJUALAN PADA UMKM - Komarudin, Mamay; Fatonah, Siti; Zahra, Surti; Widodo, Wahyu (LP2M Universitas Bina Bangsa, 2024)
Credit sales play a crucial role in enhancing the working capital and sales development of Micro, Small, and Medium Enterprises (MSMEs). Credit sales enable MSMEs to generate income before the goods or services sold are fully paid, finance daily operational activities, expand market share, and increase sales. However, credit sales also entail risks such as bad debts, defaults, and loan defaults, which can lead to financial losses for MSMEs. To mitigate these risks, MSMEs can conduct stringent credit analyses, establish clear and firm credit agreements, regularly pursue debt collections, and utilize credit insurance. These measures aid MSMEs in managing the risks associated with credit sales and enhancing the success and sustainability of their businesses